Ni/hierarchical ZSM-5 zeolites as promising systems for phenolic bio-oil upgrading: Guaiacol hydrodeoxygenation. (15th August 2020) - Li, Wenlin; Wang, Hongyan; Wu, Xiaozhuo; Betancourt, Luis E.; Tu, Chunyan; Liao, Mingjie; Cui, Xingyu; Li, Feng; Zheng, Jiajun; Li, Ruifeng
Graphical abstract: Highlights: Ni/hierarchical ZSM-5 catalyst was developed to upgrade phenolic bio-oil. Mesopores and strong acidities resulted in high catalytic HDO activity. Metal-support interaction also promoted the occurrence of HDO. The selectivity to deoxygenated products retains above 97.0% after seven cycles. Abstract: Hierarchical ZSM-5 with mesopores were derived from seed directing crystalline process. The efficient encapsulation of nickel metal was achieved by a simple incipient wetness impregnation method, and a stable Ni/hierarchical ZSM-5 hydrodeoxygenation (HDO) catalyst was fabricated. The synthesized catalysts were characterized by XRD, N2 -adsorption, FTIR, H2 -TPR, NH3 -TPD and TEM and were further tested for the hydrodeoxygenation of bio-derived guaiacol. Nickel particle size of about 6 nm and strong metal-support interaction were found for Ni/H-Z5 catalysts. It was discovered that the hydrodeoxygenation activity of the catalyst can be greatly improved by mesopores and strong acid sites. The reaction pathways were carefully studied to elucidate the effect of mesopores and acid sites. The Ni/ZSM-5 catalyst can be recycled seven times without loss of its initial selectivity.